A Influence of "All Eyes on the Judiciary" Twitter Campaigns on the Outcome of the Presidential Election Petition Tribunal in Nigeria - Onyebuchi , Alexander Chima; Etumnu, Emeka; Okoye, Loveth; Igwemeziri , Wisdom Chimeziea; Alaekwe , Kizito Nzube (COMMICAST, 2024)
In recent times, allegations of electoral and judicial fraud have been alarming. Hence, this study aims to investigate the influence of "All Eyes on the Judiciary" Twitter campaigns on the outcome of the presidential election petition tribunal in Nigeria. The public sphere theory served as the theoretical foundation for the study. In this study, the survey research method was used with a population of 5,100,000 and a sample size of 385, which was derived from the Survey Monkey online sample size calculator. A purposeful sampling technique was employed. The instrument used was an online questionnaire. The data was analysed using percentages and mean analysis. Results showed that, at an average of 74.0%, citizens are exposed to the “all eyes on the judiciary” Twitter campaigns on the outcome of the presidential election petition tribunal in Nigeria to a large extent. Findings revealed that, at a mean of 1.8 (N = 372), the “all eyes on the judiciary” Twitter campaigns did not influence the outcome of the presidential election petition tribunal in Nigeria. It was concluded that as much as the exposure of respondents to the campaigns was high, so was its usefulness. The campaign could not influence the outcome of the presidential election petition tribunal in Nigeria.